La Dame aux camélias, Lin Shu et l’arsenal de Fuzhou - Han Yiyu (Babel: Littératures Plurielles, 2023)
In the history of modern Chinese literature, Lin Shu was well-known to be a translator without knowledge of any foreign languages. His collaborators therefore played a crucial role in his translation. The present article, which essentially lays the emphasis on the collaborators of Lin Shu’s translation, attempts to reconstruct the cultural context that has made it possible for him to become the most representative translator of his era. Special attention is also paid to the importance of the Fuzhou Naval Shipyard in the Sino-French cultural exchanges.